PENGARUH KOORDINASI CAMAT TERHADAP KEBERHASILAN PROGRAM PEMBERDAYAAN MASYARAKAT DI KECAMATAN ESSANG SELATAN KABUPATEN KEPULAUAN TALAUD - PUSIDA, MAWARJATI; LENGKONG, FLORENCE DAICY; LALOMA, ALDEN (JURNAL ADMINISTRASI PUBLIK, 2019)
The aim of the research was to determine the influence of the sub-district head coordination on the success of the community empowerment program in Essang District, Talaud Islands Regency. This study uses quantitative methods. The sub-district head coordination variables are observed from indicators of communication, cooperation, synchronization, and integrity or unity of action; while the success variable of the community empowerment program is measured from indicators of welfare, access, critical awareness, participation and control. The research respondents were 40 people from the sub-district government, village government, BPD, LPM and the community. Instruments and data collection techniques using questionnaires and assisted with quide interviews. The analysis technique for hypothesis testing used statistical regression of the product moment linear regression. The results of data analysis showed regression coefficients and the sub-district head coordination variable correlation coefficient for the success of community empowerment programs in the sub-district South Essang is positive and significant, so it was concluded that the sub-district head coordination had a positive and significant correlation with the success of the community empowerment program in Essang District. Based on the results of this study, it can be recommended that sub-district head coordination in community empowerment programs needs to be improved both in program planning and implementation by streamlining the sub-district level coordination forum, conducting direct monitoring of the implementation of community empowerment programs/activities in the sub-district area, and evaluating community empowerment programs/activities in the sub-district. Keywords: Coordination, Sub-district Head, Community Empowerment.